Microprocessor technology: collection of multiple choice questions - Salam, Saifullah; Zulkifli, Mohd Faizal; Zainal Abidin, Amar Faiz; Mispan, Mohd Syafiq (Penerbit UTeM Press, 2023)
BMMA2343 Microprocessor Technology subject is designed specifically for Mechanical-based Engineering Technology students. This subject covers two fundamental fields of microprocessor technology: digital electronics and embedded systems. With almost 600 questions, this module provides comprehensive multiple choice questions.